2022
DOI: 10.3390/app12168308
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Physiognomy of Unique Sets in the Maximum Number of Repetitions Strategy—The Case of One-Arm Scott Machine Seated Bicep Curls

Abstract: The aim of this paper is to analyze the physiognomy of unique sets in the maximum number of repetitions (MNR) strategy and different correlations between the maximal forces, duration and volume for a relevant exercise in the case of a small muscle group. The research methodology proposes testing, in two phases, a total of 30 male students, for bicep curl exercises carried out on a bicep Scott machine. The obtained results showed that there were significant differences between the maximum forces (Fmax) develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Additionally, yoga improves mental health by lowering stress, anxiety, sadness, and post-traumatic stress disorder (PTSD), favoring the mental state of competition. Other authors found the same results ( Laux et al, 2015 ; Hilton et al, 2019 ; Arbo et al, 2020 ; Popa et al, 2020 ; Petre et al, 2022 ; Elkhair, A., et al, 2023 ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Additionally, yoga improves mental health by lowering stress, anxiety, sadness, and post-traumatic stress disorder (PTSD), favoring the mental state of competition. Other authors found the same results ( Laux et al, 2015 ; Hilton et al, 2019 ; Arbo et al, 2020 ; Popa et al, 2020 ; Petre et al, 2022 ; Elkhair, A., et al, 2023 ).…”
Section: Discussionsupporting
confidence: 70%
“…Attention, emotion, and yoga-inspired aspects can improve performance when combined with intellectual, metacognitive, and procedure management techniques ( Popa et al, 2020 ). Numerous factors, including load, volume, frequency, mental-physical link, contraction speed, work-rest ratio, and amount of isometric exercise duration, affect how the muscle adapts to high-level training ( Petre et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The present study showed that as athletic experience and sporting age increase, the components of autonomy improve, which we consider to have an important role in the optimization of sports performance in bodybuilding. Numerous studies on autonomy have been carried out to identify autonomy factors depending on the type of sport practiced [99][100][101], the gender of athletes [102], the manifestation of self-determination and motivation in recreational and competitive athletes [103,104], and the level of sports skills in champions [52,103]. Research on personal autonomy in athletes has also focused on identifying intrinsic and extrinsic motivations for practicing a certain type of sport and improving sports performance [105][106][107][108].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one of the main objectives of this research was to determine the applicability of these selected invasive and non-invasive tests [19] in practice and to establish their effectiveness during an annual training plan. Since these tests bring important information about the general state of an athlete's health [26] and can characterize the metabolic, cardiopulmonary and psychological responses of athletes to effort [27], their use within a well-designed protocol can direct sports training and lead to an increased effort capacity, avoid overfatigue and accidents, and maximize sports performance [28]. Furthermore, an important aspect of obtaining and maintaining the athletes' performance is to adopt well-balanced and adequate nutrition [29].…”
Section: Introductionmentioning
confidence: 99%